Reliability of magnetic fabric as paleostress indicator: a case study in Miocene lacustrine sediments from the Ebro foreland basin, N Spain - Soto, R.; Larrasoaña, J. C.; Arlegui, L. E.; Beamud, E.; Oliva, B.; Simón, J. L. (TRABAJOS DE GEOLOGÍA, 2010)
This work deals with the comparison between ASM results from weakly deformed mudrocksthat crop out at the internal part of the Ebro foreland basin and paleostress analyses obtained from faultpopulations and joint sets developed on limestone beds interbedded with the mudrocks. The coaxialityfound between the magnetic and paleostress ellipsoids shows the validity of AMS studies as paleostressindicators in foreland basins when sampling is restricted to weakly deformed mudrocks.